Collagen scaffold biomaterial patch for wound repair and preparation method thereof
Patent Information
- Application Number
- CN202611090176.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-22
AI Technical Summary
[0005]针对上述情况,为克服现有技术的缺陷,本发明提供了一种创面修复用胶原蛋白支架生物补片及其制备方法,通过引入改性硼葡酸复合物用于活化氧化葡聚糖醛基,利用硼酸酯动态交换与离子对导向效应,提高氧化葡聚糖醛基的利用率;同时结合EDC/NHS与京尼平的双层交联,形成高湿态强度、可控降解和优异的生物相容性相结合的胶原蛋白复合支架结构,有效解决了目前市场上胶原蛋白生物补片在人体内支撑性不足、降解速率与创面修复进程、戊二醛等传统交联剂带来的细胞毒性风险的问题
[0024]本方案提出了一种创面修复用胶原蛋白支架生物补片及其制备方法,通过引入的改性硼葡酸复合物中的硼酸酯基团,可与氧化葡聚糖链中被水合为偕二醇平衡态的醛基发生特异性配位交换,其中碳原子的亲电性比偕二醇更强,大幅提升与胶原蛋白中的赖ε-氨基发生亲核反应的能力,避免氧化葡聚糖丧失活性;而且改性硼葡酸复合物分子中的葡糖酸中所携带羧酸根阴离子,在弱酸性环境下与胶原蛋白中的质子化铵阳离子形成静电,吸引氧化葡聚糖醛基靠近,促进席夫碱交联反应,进一步提高氧化葡聚糖醛基的利用率,使胶原蛋白与氧化葡聚糖复合结构的密度更高、分布更均匀,进而支架生物补片结构更致密,缺陷更少,提升支架生物补片的力学性能以及降解能力。
Smart Images

Figure CN122582367B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical biomaterials technology, specifically referring to a collagen scaffold biopatch for wound repair and its preparation method. Background Technology
[0002] Collagen possesses excellent biocompatibility, low immunogenicity, and natural degradation and metabolism properties, making it one of the most promising natural biomaterials in wound repair. Currently, most collagen used to prepare biological scaffold patches is derived from animal tissues. After extraction and purification, it is processed into porous membranes, sponge-like structures, or fibrous mesh scaffolds through freeze-drying, cross-linking, and other processes. These structures serve as temporary extracellular matrix, providing structural support and a moist healing environment for cell adhesion and tissue regeneration in wounds. Furthermore, composite modification of collagen can endow scaffolds with richer physicochemical and biological functions. Currently, collagen scaffold biological patch products have been widely used in clinical practice for the repair of surgical wounds such as burns and chronic ulcers.
[0003] Although collagen-based bio-patterns have been used in clinical practice, their inherent mechanical strength is relatively low, and they are prone to swelling and softening in moist wound environments, making it difficult to maintain structural integrity under long-term exudation conditions. Cross-linking modification has therefore become necessary. However, traditional aldehyde cross-linking agents, while improving rigidity, leave residual toxicity and have low safety. Bio-based cross-linking agents such as aldehyde-modified polysaccharides have better biocompatibility, but their cross-linking efficiency is low, resulting in uneven internal mesh structure and difficulty in eliminating internal defects of the scaffold. In addition, the degradation process of collagen scaffolds in the human body is difficult to synchronize with the wound repair process. If degradation occurs too early, the scaffold will lose support prematurely, leading to repair failure. If degradation occurs too late, it is easy to cause chronic inflammation due to foreign body retention.
[0004] Therefore, there is an urgent need for a collagen wound repair material that combines good mechanical properties, controllable degradation behavior, and excellent biocompatibility, while also meeting the requirements for scaffold safety and support. Summary of the Invention
[0005] To address the above issues and overcome the shortcomings of existing technologies, this invention provides a collagen scaffold bio-patch for wound repair and its preparation method. By introducing a modified borosilicate complex to activate the oxidized dextran aldehyde group, and utilizing the dynamic exchange and ion-pair directing effect of borosilicate esters, the utilization rate of the oxidized dextran aldehyde group is improved. Simultaneously, by combining EDC / NHS with genipin in a bilayer crosslinking process, a collagen composite scaffold structure combining high wet strength, controllable degradation, and excellent biocompatibility is formed. This effectively solves the problems of insufficient support in the human body, degradation rate and wound repair process, and cytotoxic risks posed by traditional crosslinking agents such as glutaraldehyde in currently available collagen bio-patterns.
[0006] The technical solution adopted in this invention is as follows: This invention proposes a collagen scaffold biological patch for wound repair and its preparation method, comprising the following raw materials in parts by weight: 90-110 parts of type I collagen, 8-20 parts of type III collagen, 3-8 parts of chondroitin sulfate, 5-15 parts of oxidized dextran, 3-8 parts of trehalose, 0.3-1.2 parts of modified borosilicate complex, 0.8-2.5 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), 0.5-1.5 parts of N-hydroxysuccinimide (NHS), and 0.2-0.5 parts of genipin.
[0007] Furthermore, the modified borogluconic acid complex is prepared by the following method:
[0008] S1. Boric acid was pulverized into powder with D90≤10μm by air jet, and then ultrasonically dispersed in low-temperature water to prepare a suspension; D-gluconic acid-δ-lactone was dissolved in low-temperature water at the same temperature, and the degree of hydrolysis was controlled to obtain a partially hydrolyzed GDL / gluconic acid mixture.
[0009] S2. The boric acid suspension obtained in step S1 is slowly added to the GDL / gluconic acid mixture using a peristaltic pump, while titrating with a 0.2M sodium hydroxide solution to maintain the pH of the reaction system at 3.0-3.5, to carry out a reverse coprecipitation complexation reaction and form a milky white suspension.
[0010] S3. The milky white suspension obtained in step S2 is rapidly frozen and then transferred to a freeze dryer. Under vacuum conditions, it is freeze-dried according to the set heating program to obtain a fluffy powder of the modified boric acid complex.
[0011] Further, the temperature of the low-temperature water in step S1 is 2-6℃; the power of the ultrasonic dispersion is 100-200W, and the time is 5-15min; the method for controlling the degree of hydrolysis is to let it stand in an ice bath for 10-20min, and stop hydrolysis when the pH drops to 3.0-3.5, until the degree of hydrolysis is 30-40%.
[0012] Furthermore, the slow dropwise addition rate in step S2 is 0.3-0.8 mL / min; the temperature of the reverse coprecipitation complexation reaction is 2-6℃, the stirring speed is 400-800 rpm, and stirring continues for 20-40 min after the dropwise addition is completed.
[0013] Further, in step S2, the mass ratio of boric acid to D-gluconic acid-δ-lactone is 1:(2.5-4.5); the volume ratio of the boric acid suspension to the GDL / gluconic acid mixture is 1:(2-4).
[0014] Furthermore, during the rapid freezing process described in step S3, the liquid level of the suspension is maintained between 4-6 mm, and the suspension is placed in an ultra-low temperature freezer at -80℃ for 1-3 hours, with a cooling rate maintained at 3.5-5.5℃ / min; the cold trap temperature of the freeze dryer is -90 to -80℃, and the vacuum degree is 5-10 Pa.
[0015] Furthermore, the heating program in step S3 is divided into three stages: the first stage is heating from -40℃ to -10℃ at a heating rate of 0.3-0.8℃ / min and holding for 6-10 hours; the second stage is heating from -10℃ to 10℃ at a heating rate of 0.2-0.5℃ / min and holding for 4-8 hours; and the third stage is heating from 10℃ to 25℃ at a heating rate of 0.1-0.3℃ / min and holding for 2-6 hours.
[0016] Furthermore, a method for preparing a collagen scaffold biological patch for wound repair includes the following steps:
[0017] (1) Mix and stir type I collagen, type III collagen, chondroitin sulfate, oxidized dextran, trehalose and modified borate complex in an ice bath for 30-60 min, adjust the pH to 5.4-5.8 with 0.5M dilute sodium hydroxide, and then degas under vacuum at 0.05-0.07 MPa for 5-10 min to obtain homogeneous collagen complex sol;
[0018] (2) Inject 55%-65% of the volume of the composite sol into the mold, and slowly freeze it in a directional manner at a cooling rate of 0.8-1.5℃ / min on a cold table at -15℃ for 2-3 hours to form a bottom layer macroporous structure. Then, freeze it at -80℃ for 4-6 hours. Pour the remaining 35%-45% of the volume of the composite sol on top of the frozen bottom layer, and quickly freeze it to -30℃ at a cooling rate of 3-5℃ / min to form a surface microporous structure. Then freeze it in a -80℃ refrigerator for 12 hours to obtain a double-layer porous support.
[0019] (3) The bilayer porous scaffold is immersed in MES / ethanol buffer containing EDC·HCl and NHS and reacted in the dark at 15-25℃ for 2-6 hours. Then it is washed with phosphate buffer, sodium chloride solution and deionized water in sequence, and then freeze-dried to obtain EDC cross-linked semi-finished product. The EDC cross-linked semi-finished product is immersed in genipin solution and reacted in the dark at 25-37℃ for 12-24 hours. It is rinsed with deionized water until the UV absorbance of the effluent at 242nm is <0.02. It is then freeze-dried again to obtain bilayer cross-linked collagen scaffold.
[0020] (4) The double-layer cross-linked collagen scaffold is placed in a vacuum oven and subjected to deoxygenated thermal cross-linking for 12-18 hours at 100-115℃ and vacuum degree ≤0.05bar to obtain a collagen scaffold biological patch for wound repair.
[0021] Further, the MES / ethanol buffer in step (3) is a mixture of MES buffer and anhydrous ethanol, with a volume ratio of MES buffer to anhydrous ethanol of (1-2.5):1, wherein the molar concentration of MES buffer is 0.05-0.1M and the pH is 5.5; the molar ratio of EDC·HCl to collagen carboxyl groups is (3-8):1, and the molar ratio of NHS to EDC is (0.4-0.6):1.
[0022] Further, the mass concentration of the genipin solution in step (3) is 0.2%-0.5%, and a mixture of ethanol and phosphate buffered solution (PBS) is used as the solvent, wherein the volume ratio of ethanol to PBS is 3:7 and the pH value is 7.2-7.4.
[0023] The beneficial effects achieved by adopting the above solution are as follows:
[0024] This solution proposes a collagen scaffold bio-patch for wound repair and its preparation method. By introducing borate ester groups in the modified borate-glucan complex, specific coordination exchange can occur with the aldehyde groups in the oxydextran chain that are hydrated to a geminal glycol equilibrium state. The carbon atoms in this bio-patch are more electrophilic than the geminal glycols, significantly enhancing the ability to undergo nucleophilic reactions with the lys ε-amino groups in collagen and preventing the loss of activity of oxydextran. Furthermore, the carboxylate anions carried in the gluconic acid in the modified borate-glucan complex molecule form electrostatic interactions with the protonated ammonium cations in collagen under weakly acidic conditions, attracting the oxydextran aldehyde groups and promoting Schiff base cross-linking reactions. This further improves the utilization rate of the oxydextran aldehyde groups, resulting in a higher density and more uniform distribution of the collagen-oxydextran composite structure. Consequently, the scaffold bio-patch structure is denser, with fewer defects, improving the mechanical properties and degradation resistance of the scaffold bio-patch.
[0025] By improving the cross-linking efficiency of oxidized dextran through the modified borosilicate complex, the internal structure of the scaffold bio-mesh is enhanced, enabling the scaffold to maintain stability after absorbing wound exudate. Simultaneously, the borosilicate esters formed during the reaction of the modified borosilicate complex stabilize the already generated Schiff base imine bonds, slightly raising the hydrolysis barrier of the imine bonds, delaying the scaffold degradation time in vivo, and effectively inhibiting the degradation rate. This ensures the scaffold maintains sufficient structural integrity in the early stages of implantation to support cell migration and angiogenesis. With the development of granulation tissue, the scaffold degrades gradually, and degradation products are eliminated through normal metabolic pathways, avoiding premature scaffold failure due to excessively rapid degradation or foreign body retention due to excessively slow degradation. This creates a good synchronization with the wound repair time window, achieving a smooth transition from the inflammatory phase to the proliferative phase, thus improving the lifespan and support effect of the scaffold bio-mesh.
[0026] Based on biomaterials such as collagen, the modified boron-gluconic acid complex is composed of boric acid and D-gluconic acid, both of which are safe pharmaceutical-grade raw materials. No new toxic intermediates are generated during the reaction, and there is no risk of cytotoxicity caused by residual aldehyde groups in traditional biological patches such as glutaraldehyde. After the reaction, unbound free matter can be removed by washing, and the residual boron in the final scaffold biological patch is far below the safety threshold. In addition, genipin, as a cross-linking agent derived from natural plants, releases non-toxic metabolites when its cross-linking products degrade in vivo, and can be excreted through the kidneys, further reducing safety risks. This allows the scaffold to have sufficient strength to withstand clinical operations and in vivo mechanical environment, while its cytotoxicity, hemolysis rate, and sensitization indicators are all superior to relevant medical device standards. Attached Figure Description
[0027] Figure 1 The images show the SEM microstructures of various samples of the collagen scaffold biopatch for wound repair proposed in this invention; wherein, A is a partial SEM microstructure of Example 1, B is a partial SEM microstructure of Comparative Example 2, C is a partial SEM microstructure of Comparative Example 3, D is a magnified partial SEM microstructure of Example 1, E is a magnified partial SEM microstructure of Comparative Example 2, and F is a magnified partial SEM microstructure of Comparative Example 3.
[0028] Figure 2 The images show the EDS and mass spectra of a modified boron gluconic acid complex for a collagen scaffold biopatch for wound repair proposed in this invention; wherein, A is the EDS energy spectrum of the modified boron gluconic acid complex, B is the mass spectrum of the modified boron gluconic acid complex, C is the SEM microstructure of the modified boron gluconic acid complex, D is the surface distribution map of boron (B), E is the surface distribution map of carbon (C), and F is the surface distribution map of oxygen (O).
[0029] Figure 3This is a comparison chart of the mass residue rates of various samples of the collagen scaffold biological patch for wound repair proposed in this invention during in vitro degradation experiments.
[0030] Figure 4 The figures show the experimental results of mechanical compression tests on various samples of a collagen scaffold biological patch for wound repair proposed in this invention.
[0031] Figure 5 This is a comparison chart of pH changes in the degradation solution of various samples of a collagen scaffold biopatch for wound repair proposed in this invention.
[0032] Figure 6 This is a comparison chart of the swelling rate of various samples of the collagen scaffold biological patch for wound repair proposed in this invention, showing the changes in crosslinking density.
[0033] Figure 7 This is a comparative graph showing the volume shrinkage rate and enzymatic hydrolysis rate of various samples of the collagen scaffold biological patch for wound repair proposed in this invention.
[0034] Figure 8 This is a comparative diagram of the cytotoxicity test results of various samples of the collagen scaffold biological patch for wound repair proposed in this invention.
[0035] Figure 9 The image shows the results of hemolysis experiments on various samples of a collagen scaffold biological patch for wound repair proposed in this invention.
[0036] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation
[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention were purchased through commercial channels.
[0039] The type I collagen (bovine, lyophilized powder, ≥90%) used in this invention was purchased from Jiaxing Hengjie Biopharmaceutical Co., Ltd.; the type III collagen (bovine, lyophilized powder, ≥95%) was purchased from Jiekang Gelatin Co., Ltd.; chondroitin sulfate (porcine cartilage, ≥90%, USP grade) was purchased from Jiaxing Hengjie Biopharmaceutical Co., Ltd.; oxidized dextran (degree of substitution 35±10%) was purchased from the Suzhou EngineeringForLife (EFL) reagent platform; trehalose (anhydrous, ≥99%) was purchased from Jiangsu Aogu Biotechnology Co., Ltd.; EDC·HCl (≥98%) was purchased from Beijing Bio-Lab Technology Co., Ltd.; NHS (≥98%) was purchased from Beijing Bio-Lab Technology Co., Ltd.; and genipin (HPLC ≥98%) was purchased from Guangxi Shanyun Biochemical Technology Co., Ltd.
[0040] Example 1:
[0041] A collagen scaffold biopatch for wound repair and its preparation method
[0042] In this embodiment, a collagen scaffold biopatch for wound repair is prepared. Before preparation, a modified boric acid-gluconic acid complex is prepared for later use. Boric acid is pulverized into powder with D90≤10μm by air jet, and then ultrasonically dispersed in low-temperature water at 2℃ for 15min at 100W to prepare a suspension. D-gluconic acid-δ-lactone is dissolved in low-temperature water at the same temperature and allowed to stand in an ice bath for 10min to control the degree of hydrolysis to 30%, thus obtaining a partially hydrolyzed GDL / gluconic acid mixture.
[0043] The obtained boric acid suspension was added dropwise to the GDL / gluconic acid mixture at a rate of 0.3 mL / min using a peristaltic pump, while simultaneously titrating with a 0.2 M sodium hydroxide solution to maintain the pH of the reaction system at 3.0-3.5. A reverse coprecipitation complexation reaction was carried out under stirring conditions of 2 °C and 400 rpm. After the addition was complete, stirring was continued for 40 min to form a milky white suspension. The mass ratio of boric acid to D-gluconic acid-δ-lactone was 1:2.5, and the volume ratio of the boric acid suspension to the GDL / gluconic acid mixture was 1:2.
[0044] The resulting milky white suspension was kept at a liquid level of 4 mm and rapidly frozen in an ultra-low temperature freezer at -80℃ at a cooling rate of 3.5℃ / min for 3 hours. Then, it was transferred to a freeze dryer with a cold trap temperature of -90℃ and a vacuum degree of 5 Pa and freeze-dried according to the set heating program: the first stage was from -40℃ to -10℃ at a heating rate of 0.3℃ / min and held for 10 hours; the second stage was from -10℃ to 10℃ at a heating rate of 0.2℃ / min and held for 8 hours; the third stage was from 10℃ to 25℃ at a heating rate of 0.1℃ / min and held for 6 hours, resulting in a fluffy powder of the modified borogluconic acid complex.
[0045] Subsequently, a collagen scaffold was prepared and cross-linked. 90 parts of type I collagen, 8 parts of type III collagen, 3 parts of chondroitin sulfate, 5 parts of oxidized dextran, 3 parts of trehalose and 0.3 parts of modified borosilicate complex were mixed and stirred in an ice bath for 30 min. The pH was adjusted to 5.4 with 0.5M dilute sodium hydroxide. Then, the mixture was degassed under vacuum at 0.05 MPa for 10 min to obtain a homogeneous collagen composite sol.
[0046] 55% of the volume of the composite sol was injected into the mold and slowly directionally frozen at a cooling rate of 0.8℃ / min for 3 hours on a -15℃ cold stage to form a bottom macroporous structure. Then it was frozen at -80℃ for 4 hours. The remaining 45% of the volume of the composite sol was poured on top of the frozen bottom layer and rapidly frozen to -30℃ at a cooling rate of 3℃ / min to form a surface microporous structure. It was then frozen at -80℃ for 12 hours to obtain a double-layer porous scaffold.
[0047] The bilayer porous scaffold was immersed in a MES / ethanol buffer containing 0.8 parts EDC·HCl and 0.5 parts NHS, wherein the MES / ethanol buffer was a mixture of MES buffer and anhydrous ethanol in a volume ratio of 1:1, the molar concentration of the MES buffer was 0.05M, the pH was 5.5, the molar ratio of EDC·HCl to collagen carboxyl groups was 3:1, and the molar ratio of NHS to EDC was 0.4:1. The reaction was carried out at 15°C in the dark for 6 hours, and then washed sequentially with phosphate buffer, sodium chloride solution and deionized water. After lyophilization, the EDC cross-linked semi-finished product was obtained.
[0048] 0.2 parts of genipin were dissolved in a mixture of ethanol and PBS to prepare a genipin solution with a mass concentration of 0.2%, wherein the volume ratio of ethanol to PBS was 3:7 and the pH value was 7.2. The EDC cross-linked semi-finished product was then immersed in the genipin solution and reacted at 25°C in the dark for 24 hours. The product was then rinsed with deionized water until the UV absorbance of the effluent at 242 nm was <0.02. The product was then freeze-dried again to obtain a bilayer cross-linked collagen scaffold.
[0049] The double-layer cross-linked collagen scaffold was placed in a vacuum oven and subjected to deoxygenated thermal cross-linking at 100°C and a vacuum degree ≤0.05 bar for 18 hours to obtain a collagen scaffold biological patch for wound repair.
[0050] Example 2:
[0051] A collagen scaffold biopatch for wound repair and its preparation method
[0052] In this embodiment, a collagen scaffold biopatch for wound repair is prepared. Before preparation, a modified boric acid-gluconic acid complex is prepared for later use. Boric acid is pulverized into powder with D90≤10μm by air jet, and then ultrasonically dispersed in low-temperature water at 4℃ for 10min to prepare a suspension. D-gluconic acid-δ-lactone is dissolved in low-temperature water at the same temperature, and allowed to stand in an ice bath for 15min to control the degree of hydrolysis to 35%, thus obtaining a partially hydrolyzed GDL / gluconic acid mixture.
[0053] The obtained boric acid suspension was added dropwise to the GDL / gluconic acid mixture at a rate of 0.55 mL / min using a peristaltic pump, while simultaneously titrating with a 0.2 M sodium hydroxide solution to maintain the pH of the reaction system at 3.0-3.5. A reverse coprecipitation complexation reaction was carried out under stirring conditions of 4 °C and 600 rpm. After the addition was complete, stirring was continued for 30 min to form a milky white suspension. The mass ratio of boric acid to D-gluconic acid-δ-lactone was 1:3.5, and the volume ratio of the boric acid suspension to the GDL / gluconic acid mixture was 1:3.
[0054] The resulting milky white suspension was kept at a liquid level of 5 mm and rapidly frozen in an ultra-low temperature freezer at -80℃ at a cooling rate of 4.5℃ / min for 2 hours. Then, it was transferred to a freeze dryer with a cold trap temperature of -85℃ and a vacuum degree of 7.5 Pa and freeze-dried according to the set heating program: the first stage was from -40℃ to -10℃ at a heating rate of 0.6℃ / min and held for 8 hours; the second stage was from -10℃ to 10℃ at a heating rate of 0.35℃ / min and held for 6 hours; the third stage was from 10℃ to 25℃ at a heating rate of 0.2℃ / min and held for 4 hours, resulting in a fluffy powder of the modified borosilicate complex.
[0055] Subsequently, a collagen scaffold was prepared and cross-linked. 100 parts of type I collagen, 14 parts of type III collagen, 5.5 parts of chondroitin sulfate, 10 parts of oxidized dextran, 5.5 parts of trehalose and 0.75 parts of modified borosilicate complex were mixed and stirred in an ice bath for 45 min. The pH was adjusted to 5.6 with 0.5M dilute sodium hydroxide. Then, the mixture was degassed under vacuum at 0.06 MPa for 7.5 min to obtain a homogeneous collagen composite sol.
[0056] 60% of the volume of the composite sol was injected into the mold and slowly directionally frozen at a cooling rate of 1.2℃ / min for 2.5 hours on a -15℃ cold stage to form a bottom macroporous structure. Then it was frozen at -80℃ for 5 hours. The remaining 40% of the volume of the composite sol was poured on top of the frozen bottom layer and rapidly frozen to -30℃ at a cooling rate of 4℃ / min to form a surface microporous structure. It was then frozen at -80℃ for 12 hours to obtain a double-layer porous scaffold.
[0057] The bilayer porous scaffold was immersed in a MES / ethanol buffer containing 1.7 parts EDC·HCl and 1.0 parts NHS, wherein the MES / ethanol buffer was a mixture of MES buffer and anhydrous ethanol at a volume ratio of 1.75:1, the molar concentration of the MES buffer was 0.075M, the pH was 5.5, the molar ratio of EDC·HCl to collagen carboxyl groups was 5.5:1, and the molar ratio of NHS to EDC was 0.5:1. The reaction was carried out at 20°C in the dark for 4 hours, and then washed sequentially with phosphate buffer, sodium chloride solution and deionized water. After lyophilization, the EDC cross-linked semi-finished product was obtained.
[0058] 0.35 parts of genipin were dissolved in a mixture of ethanol and PBS to prepare a genipin solution with a mass concentration of 0.35%, wherein the volume ratio of ethanol to PBS was 3:7 and the pH value was 7.3. The EDC cross-linked semi-finished product was then immersed in the genipin solution and reacted at 31°C in the dark for 18 hours. The product was then rinsed with deionized water until the UV absorbance of the effluent at 242 nm was <0.02. The product was then freeze-dried again to obtain a bilayer cross-linked collagen scaffold.
[0059] The double-layer cross-linked collagen scaffold was placed in a vacuum oven and subjected to deoxygenated thermal cross-linking at 107.5°C and a vacuum degree ≤0.05 bar for 15 hours to obtain a collagen scaffold biological patch for wound repair.
[0060] Example 3:
[0061] A collagen scaffold biopatch for wound repair and its preparation method
[0062] In this embodiment, a collagen scaffold biopatch for wound repair is prepared. Before preparation, a modified boric acid-gluconic acid complex is prepared for later use. Boric acid is pulverized into powder with D90≤10μm by air jet, and then ultrasonically dispersed in low-temperature water at 6℃ for 5min at 200W power to prepare a suspension. D-gluconic acid-δ-lactone is dissolved in low-temperature water at the same temperature, and the hydrolysis degree is controlled to 40% by standing in an ice bath for 20min to obtain a partially hydrolyzed GDL / gluconic acid mixture.
[0063] The obtained boric acid suspension was added dropwise to the GDL / gluconic acid mixture at a rate of 0.8 mL / min using a peristaltic pump, while simultaneously titrating with a 0.2 M sodium hydroxide solution to maintain the pH of the reaction system at 3.0-3.5. A reverse coprecipitation complexation reaction was carried out under stirring conditions of 6 °C and 800 rpm. After the addition was complete, stirring was continued for 20 min to form a milky white suspension. The mass ratio of boric acid to D-gluconic acid-δ-lactone was 1:4.5, and the volume ratio of the boric acid suspension to the GDL / gluconic acid mixture was 1:4.
[0064] The resulting milky white suspension was kept at a liquid level of 6 mm and rapidly frozen in an ultra-low temperature freezer at -80℃ at a cooling rate of 5.5℃ / min for 1 h. Then, it was transferred to a freeze dryer with a cold trap temperature of -80℃ and a vacuum degree of 10 Pa and freeze-dried according to the set heating program: the first stage was from -40℃ to -10℃ at a heating rate of 0.8℃ / min and held for 6 h; the second stage was from -10℃ to 10℃ at a heating rate of 0.5℃ / min and held for 4 h; the third stage was from 10℃ to 25℃ at a heating rate of 0.3℃ / min and held for 2 h, resulting in a fluffy powder of the modified borogluconic acid complex.
[0065] Subsequently, a collagen scaffold was prepared and cross-linked. 110 parts of type I collagen, 20 parts of type III collagen, 8 parts of chondroitin sulfate, 15 parts of oxidized dextran, 8 parts of trehalose and 1.2 parts of modified borosilicate complex were mixed and stirred in an ice bath for 60 min. The pH was adjusted to 5.8 with 0.5M dilute sodium hydroxide. Then, the mixture was degassed under vacuum at 0.07 MPa for 5 min to obtain a homogeneous collagen composite sol.
[0066] 65% of the volume of the composite sol was injected into the mold and slowly directionally frozen at a cooling rate of 1.5℃ / min for 2 hours on a -15℃ cold stage to form a bottom macroporous structure. Then it was frozen at -80℃ for 6 hours. The remaining 35% of the volume of the composite sol was poured on top of the frozen bottom layer and rapidly frozen to -30℃ at a cooling rate of 5℃ / min to form a surface microporous structure. It was then frozen at -80℃ for 12 hours to obtain a double-layer porous scaffold.
[0067] The bilayer porous scaffold was immersed in a MES / ethanol buffer solution containing 2.5 parts EDC·HCl and 1.5 parts NHS. The MES / ethanol buffer solution was a mixture of MES buffer and anhydrous ethanol at a volume ratio of 2.5:1. The molar concentration of the MES buffer solution was 0.1M and the pH was 5.5. The molar ratio of EDC·HCl to collagen carboxyl groups was 8:1, and the molar ratio of NHS to EDC was 0.6:1. The reaction was carried out at 25°C in the dark for 2 hours. Then, it was washed sequentially with phosphate buffer, sodium chloride solution, and deionized water. After lyophilization, the EDC cross-linked semi-finished product was obtained.
[0068] 0.5 parts of genipin were dissolved in a mixture of ethanol and PBS to prepare a genipin solution with a mass concentration of 0.5%, wherein the volume ratio of ethanol to PBS was 3:7 and the pH value was 7.4. The EDC cross-linked semi-finished product was then immersed in the genipin solution and reacted at 37°C in the dark for 12 hours. The product was then rinsed with deionized water until the UV absorbance of the effluent at 242 nm was <0.02. The product was then freeze-dried again to obtain a bilayer cross-linked collagen scaffold.
[0069] The double-layer cross-linked collagen scaffold was placed in a vacuum oven and subjected to deoxygenated thermal cross-linking at 115°C and a vacuum degree ≤0.05 bar for 12 hours to obtain a collagen scaffold biological patch for wound repair.
[0070] Comparative Example 1:
[0071] The specific implementation method is the same as in Example 1, except that: no modified boric acid complex is added, and the other raw materials and process parameters remain unchanged.
[0072] This comparative example completely removes the modified borate complex to verify whether it has a significant impact on the mechanical properties, degradation rate, and cell compatibility of the scaffold, thereby verifying whether the modified borate complex is necessary.
[0073] Comparative Example 2:
[0074] The specific implementation method is the same as in Example 1, except that the modified boron glucan complex and oxidized dextran are replaced with an equal mass of glutaraldehyde (mass concentration 0.5%), and glutaraldehyde is added directly during ice bath mixing, while the other process parameters remain the same.
[0075] This comparative example compares the effects of glutaraldehyde in the modified borosilicate complex and oxidized dextran to determine whether there are significant differences in their crosslinking effects, mechanical properties, degradation efficiency, and biosafety.
[0076] Comparative Example 3:
[0077] The specific implementation method is the same as in Example 1, except that the modified boroglucan complex is retained, oxidized dextran is not added, and the other raw materials and process parameters remain unchanged.
[0078] This comparative example removes oxidized dextran while retaining the modified borosilicate complex alone. The comparison example and the comparative example are compared to see if there are significant differences in crosslinking density, mechanical strength, and exfoliation efficiency, thereby verifying whether there is a better synergistic scale-up effect between the modified borosilicate complex and oxidized dextran.
[0079] Experimental Example 1:
[0080] Preparation of experimental samples: Scaffold biological patch samples were prepared according to the preparation methods of Examples 1, 2, 3 and Comparative Examples 1, 2, and 3, with 6 parallel samples prepared for each group.
[0081] Observation of microstructure using scanning electron microscopy (SEM):
[0082] Each group of scaffold samples was cut into small pieces of 5mm×5mm×2mm, fixed to the sample stage with conductive adhesive, and sputtered with gold (current 20mA, time 60s). The cross-section and surface morphology of the scaffold were observed using a scanning electron microscope at an accelerating voltage of 5kV, with a focus on observing the pore distribution, pore size and pore wall density. Three fields of view were randomly selected, and the average pore size and porosity were statistically analyzed.
[0083] Mechanical compression test:
[0084] Each group of support samples was made into cylinders with a diameter of 10 mm and a height of 8 mm, with 6 samples per group; a universal testing machine was used to compress the samples to 70% of their original height at a compression rate of 1 mm / min; the stress-strain curves were recorded, and the elastic modulus (slope of the linear segment) and compressive strength (stress at 30% strain) were calculated.
[0085] Porosity determination (liquid displacement method):
[0086] Weigh the dryer rack (Wd), immerse the rack in anhydrous ethanol, degas under vacuum for 10 minutes to ensure full saturation, remove it, blot off excess ethanol with filter paper, and weigh the wet weight (Ww); calculate the wet weight using the formula: , where V_scaffold is the apparent volume of the scaffold biopatch.
[0087] In vitro degradation experiment:
[0088] Each group of scaffolds (initial mass M0) was immersed in PBS solution containing 0.5 U / mL collagenase to accelerate degradation. The pH was adjusted to 7.4, and the scaffolds were placed in a constant temperature shaking incubator at 100 rpm and 37°C. The scaffolds were removed every 24 hours, rinsed three times with deionized water, freeze-dried, and weighed Mt. The residual mass rate (%) was calculated as M0 / Mt × 100%, and this process was repeated for 7 days.
[0089] Table 1. SEM microstructure characteristics and porosity
[0090]
[0091] Experimental results are as follows Figure 1 , Figure 2 , Figure 3 , Figure 4As shown in Table 1, the collagen scaffold bio-patterns prepared in Examples 1-3 exhibited denser pore walls and a more uniform pore distribution in their microstructure. Their average pore size was significantly smaller than that of the comparative groups, and their porosity was also correspondingly lower. Mechanical tests showed that the elastic modulus and compressive strength of the Example groups were significantly higher than those of all the comparative groups. Among them, Comparative Example 3 had the worst mechanical properties due to the lack of oxidized dextran, Comparative Example 1 had relatively weak strength due to the lack of modified borosilicate complex, and Comparative Example 2 had a slightly improved mechanical strength after replacing it with glutaraldehyde, but it was still not as good as that of the Example groups. In vitro degradation experiments further showed that the degradation rate of the Example groups was the slowest, especially in the first 72 hours when the mass retention rate was the highest. Comparative Examples 1 and 3 degraded rapidly, while the degradation curve of Comparative Example 2 was in between. These results together indicate that the introduction of modified borosilicate complex and its synergistic effect with oxidized dextran can effectively improve the structural density and mechanical strength of the scaffold, while giving the scaffold a more stable degradation ability. This meets the needs of the scaffold bio-pattern during wound repair, from early support to gradual degradation in the later stages.
[0092] Experimental Example 2:
[0093] Preparation of experimental samples: Scaffold biopatch samples were prepared according to the preparation methods of Examples 1, 2, 3 and Comparative Examples 1, 2, and 3, with 6 parallel samples in each group.
[0094] pH change monitoring of degradation solution:
[0095] Each group of scaffolds (initial mass M0) was immersed in SBF at pH 7.4 and 37℃ to simulate a body fluid environment and placed in a constant temperature shaker at a shaking rate of 50 rpm. The pH value of the degradation solution was measured with a pH meter on days 0, 1, 3, 5, 7, 14, 21, and 28, and the trend of change was recorded. pH-time curves were plotted to compare the release rate of degradation products in each group.
[0096] Stent volume shrinkage rate determination:
[0097] Before degradation, the length, width, and height of each group of stents were measured with vernier calipers, and the initial volume V0 was calculated. The stents were removed on days 7, 14, 21, and 28, and the surface moisture was absorbed with filter paper. The volume shrinkage rate was calculated as (V0−Vt) / V0×100%. The smaller the volume shrinkage rate, the more stable the stent structure and the stronger its resistance to collapse.
[0098] Crosslinking density change (swelling rate method): Before degradation and on days 7 and 14 of degradation, scaffold samples (3 per group) were taken, lyophilized and weighed Wd; the samples were immersed in PBS at pH 7.4 and 37℃ for 24h to allow them to fully swell, and after removal, the surface moisture was absorbed with filter paper and weighed Ws; the swelling rate was calculated as (Ws−Wd) / Wd×100%.
[0099] Determination of enzymatic hydrolysis kinetic parameters:
[0100] Each group of scaffolds (initial mass M0) was immersed in Tris-HCl buffer at 37℃ and placed in a constant temperature shaker with a shaking speed of 100 rpm. The Tris-HCl buffer had a pH of 7.4 and contained 10 mM calcium chloride and 1 U / mL type I collagenase. Every 30 min, 100 μL of the degradation solution was taken out, and the content of soluble protein released was determined by the Lowry method. An equal volume of fresh enzyme solution was added. The degradation rate constant k was calculated by fitting the first-order kinetic equation ln(M0 / Mt)=kt based on the cumulative protein release. The values of k for each group were compared. The smaller the k value, the slower the degradation and the stronger the resistance of the scaffold to enzymatic hydrolysis.
[0101] Experimental results are as follows Figure 5 , Figure 6 , Figure 7 As shown, Examples 1-3 exhibited excellent characteristics in all test dimensions. The pH value of their degradation solution showed a gradual decreasing trend throughout the cycle, indicating that the degradation process was mild and controllable. The scaffold volume shrinkage rate remained at a low level, reflecting good structural anti-collapse ability. The swelling rate increase was small, indicating that it could maintain high stability during degradation. The enzymatic hydrolysis rate constant was small, demonstrating strong resistance to enzymatic hydrolysis. In contrast, Comparative Example 1 showed significant changes in all indicators, with a rapid decrease in pH, a large volume shrinkage, an increase in swelling rate, and a significantly higher enzymatic hydrolysis rate, indicating that the scaffold structure became unstable and disintegrated rapidly. Comparative Example 2 showed that some parameters hardly changed over time, indicating a slow degradation process that could not meet the needs of gradual tissue ingrowth. Comparative Example 3 performed better overall than Comparative Examples 1 and 2, but still showed a significant gap compared to the Examples. The above results indicate that the scaffold bio-patch structure of the Examples is stable, has good degradation efficiency, and achieves a good match between degradation rate and wound repair time.
[0102] Experimental Example 3:
[0103] Experimental samples: Scaffold bio-patch samples were prepared according to the preparation methods of Examples 1, 2, 3 and Comparative Examples 1, 2, and 3, with 6 parallel samples in each group. A negative control group (sterile PBS) and a positive control group (culture medium containing 5% DMSO) were also set up.
[0104] Cytotoxicity assay (MTT method):
[0105] Each scaffold was cut into circular pieces with a diameter of 6 mm and a thickness of 1 mm, sterilized with ethylene oxide, and placed in 48-well plates. L929 mouse fibroblasts (density 1×10⁴ cells / well) were inoculated and cultured in DMEM medium containing 10% FBS and 5% CO₂ at 37°C. After 24 h, 48 h, and 72 h of culture, 20 μL of MTT solution (5 mg / mL) was added to each well, and incubation was continued for another 4 h. The supernatant was discarded, and 150 μL of DMSO was added to dissolve formazan crystals. The absorbance (OD value) was measured at 570 nm. The relative cell proliferation rate was calculated and graded according to GB / T 16886.5 standard (≥75% is acceptable).
[0106] Hemolysis test:
[0107] Fresh blood was collected from New Zealand rabbits, anticoagulated with heparin, and diluted to 2% (v / v) with physiological saline. Each group of scaffolds (10mm×10mm×2mm) was placed in a test tube, 10mL of physiological saline was added, and the tubes were preheated at 37℃ for 30min. 0.2mL of diluted rabbit blood was added to each tube, and the tubes were incubated at 37℃ for 60min. After centrifugation, the supernatant was measured at 545nm. A positive control was distilled water with added blood cells, and a negative control was physiological saline with added blood cells. The hemolysis rate (%) was calculated as: (Experimental group OD - Negative group OD) / (Positive group OD - Negative group OD) × 100%.
[0108] Skin sensitization test:
[0109] Hartley guinea pigs (half male and half female), 6 in each group; the scaffold extract (0.1 g / mL, extracted at 37℃ for 24 h) of each group was mixed with an equal volume of Freund's complete adjuvant, and 0.1 mL was injected intradermally into the scapular mesothelial space; local induction: 7 days later, the scaffold extract was applied to the induction site and covered with an occlusive dressing for 48 h; 14 days later, the scaffold extract was applied to the untreated area of the abdomen, and erythema and edema were observed after 24 h and 48 h, and scored according to the Magnusson-Kligman grading (0-4); the sensitization rate was required to be ≤8% (i.e., grade 0 or 1 reactions accounted for the vast majority).
[0110] Determination of residual boron content:
[0111] Take approximately 0.5 g of each group of stent samples and digest them using microwave digestion (nitric acid + hydrogen peroxide). Determine the boron content in the digestion solution using inductively coupled plasma mass spectrometry (ICP-MS) and calculate the boron residue in the stent (μg / g). According to the YY / T0771.1 standard, the boron residue should be less than 10 μg / g.
[0112] Table 2 Results of skin sensitization test
[0113]
[0114] Experimental results are as follows Figure 8 , Figure 9 As shown in Table 2, the collagen scaffold biopatch prepared in the embodiments of the present invention exhibited excellent safety in all test items. In the cytotoxicity experiment, the relative cell proliferation rate of Examples 1-3 was significantly higher than that of Comparative Examples 1 and 3, while Comparative Example 2 showed obvious cytotoxicity and cell survival rate was lower than that of the Example group. The hemolysis experiment showed that the hemolysis rate of the Example group was maintained at a low level, which was better than that of the Comparative Example. In the skin sensitization experiment, only very slight individual reactions were observed in the Example group, and no obvious sensitization phenomenon was observed, while Comparative Example 2 showed a more serious sensitization reaction. The boron element residual content determination showed that the boron content detected in the Example group and Comparative Example 3 was far below the safety threshold. In summary, the synergistic effect of the modified boron gluconic acid complex and oxidized dextran plays an important role in maintaining excellent cell compatibility and blood compatibility. Therefore, the scaffold biopatch prepared in the present invention has good biocompatibility and its safety is significantly better than that of the traditional method using glutaraldehyde crosslinking.
[0115] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0116] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
[0117] The present invention and its embodiments have been described above. This description is not restrictive. The accompanying drawings are only one embodiment of the present invention. The actual structure is not limited to this. In short, if a person skilled in the art is inspired by this description and designs a similar structure and embodiment without departing from the spirit of the present invention, such design should fall within the protection scope of the present invention.
Claims
1. A collagen scaffold biological patch for wound repair, characterized in that: The raw materials include the following parts by weight: 90-110 parts of type I collagen, 8-20 parts of type III collagen, 3-8 parts of chondroitin sulfate, 5-15 parts of oxidized dextran, 3-8 parts of trehalose, 0.3-1.2 parts of modified borosilicate complex, 0.8-2.5 parts of EDC·HCl, 0.5-1.5 parts of NHS, and 0.2-0.5 parts of genipin; The modified borogluconic acid complex was prepared using the following method: S1. Boric acid is pulverized into powder with D90≤10μm using an air jet, and then ultrasonically dispersed in low-temperature water to prepare a boric acid suspension; D-gluconic acid-δ-lactone is dissolved in low-temperature water at the same temperature, and the degree of hydrolysis is controlled to be 30-40% to obtain a partially hydrolyzed GDL / gluconic acid mixture; the temperature of the low-temperature water is 2-6℃; S2. The boric acid suspension obtained in step S1 is slowly added to the GDL / gluconic acid mixture using a peristaltic pump, while titrating with a 0.2M sodium hydroxide solution to maintain the pH of the reaction system at 3.0-3.
5. A reverse coprecipitation complexation reaction is carried out under stirring to form a milky white suspension. S3. The milky white suspension obtained in step S2 is rapidly frozen and then transferred to a freeze dryer. Under vacuum conditions, it is freeze-dried according to the set heating program to obtain a fluffy powder of the modified boric acid complex. In step S1, the mass ratio of boric acid to D-gluconic acid-δ-lactone is 1:(2.5-4.5); in step S2, the volume ratio of the boric acid suspension to the GDL / gluconic acid mixture is 1:(2-4). The method for preparing a collagen scaffold bio-patch for wound repair includes the following steps: (1) Mix and stir type I collagen, type III collagen, chondroitin sulfate, oxidized dextran, trehalose and modified borate complex in an ice bath for 30-60 min, adjust the pH to 5.4-5.8 with 0.5M dilute sodium hydroxide, and then degas under vacuum at 0.05-0.07 MPa for 5-10 min to obtain homogeneous collagen complex sol; (2) Inject 55%-65% of the volume of the composite sol into the mold, and slowly freeze it in a directional manner at a cooling rate of 0.8-1.5℃ / min on a cold table at -15℃ for 2-3 hours to form a bottom layer macroporous structure. Then, freeze it at -80℃ for 4-6 hours. Pour the remaining 35%-45% of the volume of the composite sol on top of the frozen bottom layer, and quickly freeze it to -30℃ at a cooling rate of 3-5℃ / min to form a surface microporous structure. Then freeze it in a -80℃ refrigerator for 12 hours to obtain a double-layer porous support. (3) The bilayer porous scaffold is immersed in MES / ethanol buffer containing EDC·HCl and NHS and reacted in the dark at 15-25℃ for 2-6 hours. Then it is washed with phosphate buffer, sodium chloride solution and deionized water in sequence, and then freeze-dried to obtain EDC cross-linked semi-finished product. The EDC cross-linked semi-finished product is immersed in genipin solution and reacted in the dark at 25-37℃ for 12-24 hours. It is rinsed with deionized water until the UV absorbance of the effluent at 242nm is <0.
02. It is then freeze-dried again to obtain bilayer cross-linked collagen scaffold. (4) The double-layer cross-linked collagen scaffold is placed in a vacuum oven and subjected to deoxygenated thermal cross-linking for 12-18 hours at 100-115℃ and vacuum degree ≤0.05bar to obtain a collagen scaffold biological patch for wound repair.
2. The collagen scaffold biological patch for wound repair according to claim 1, characterized in that: The ultrasonic dispersion in step S1 has a power of 100-200W and a time of 5-15min; the method for controlling the degree of hydrolysis is to let it stand in an ice bath for 10-20min, and stop hydrolysis when the pH drops to 3.0-3.
5.
3. The collagen scaffold biological patch for wound repair according to claim 1, characterized in that: The slow dropwise addition rate in step S2 is 0.3-0.8 mL / min; the temperature of the reverse coprecipitation complexation reaction is 2-6℃, the stirring speed is 400-800 rpm, and stirring continues for 20-40 min after the dropwise addition is completed.
4. The collagen scaffold biological patch for wound repair according to claim 1, characterized in that: During the rapid freezing process described in step S3, the liquid level of the suspension is maintained between 4-6 mm, and the suspension is placed in an ultra-low temperature freezer at -80℃ for 1-3 hours, with a cooling rate of 3.5-5.5℃ / min; the cold trap temperature of the freeze dryer is -90 to -80℃, and the vacuum degree is 5-10 Pa.
5. The collagen scaffold biological patch for wound repair according to claim 1, characterized in that: The heating program described in step S3 is divided into three stages: the first stage is heating from -40℃ to -10℃ at a heating rate of 0.3-0.8℃ / min and holding for 6-10 hours; the second stage is heating from -10℃ to 10℃ at a heating rate of 0.2-0.5℃ / min and holding for 4-8 hours; and the third stage is heating from 10℃ to 25℃ at a heating rate of 0.1-0.3℃ / min and holding for 2-6 hours.
6. A method for preparing a collagen scaffold bio-patch for wound repair, wherein the method is used to prepare the collagen scaffold bio-patch for wound repair as described in any one of claims 1-5, characterized in that: Includes the following steps: (1) Mix and stir type I collagen, type III collagen, chondroitin sulfate, oxidized dextran, trehalose and modified borate complex in an ice bath for 30-60 min, adjust the pH to 5.4-5.8 with 0.5M dilute sodium hydroxide, and then degas under vacuum at 0.05-0.07 MPa for 5-10 min to obtain homogeneous collagen complex sol; (2) Inject 55%-65% of the volume of the composite sol into the mold, and slowly freeze it in a directional manner at a cooling rate of 0.8-1.5℃ / min on a cold table at -15℃ for 2-3 hours to form a bottom layer macroporous structure. Then, freeze it at -80℃ for 4-6 hours. Pour the remaining 35%-45% of the volume of the composite sol on top of the frozen bottom layer, and quickly freeze it to -30℃ at a cooling rate of 3-5℃ / min to form a surface microporous structure. Then freeze it in a -80℃ refrigerator for 12 hours to obtain a double-layer porous support. (3) The bilayer porous scaffold is immersed in MES / ethanol buffer containing EDC·HCl and NHS and reacted in the dark at 15-25℃ for 2-6 hours. Then it is washed with phosphate buffer, sodium chloride solution and deionized water in sequence, and then freeze-dried to obtain EDC cross-linked semi-finished product. The EDC cross-linked semi-finished product is immersed in genipin solution and reacted in the dark at 25-37℃ for 12-24 hours. It is rinsed with deionized water until the UV absorbance of the effluent at 242nm is <0.
02. It is then freeze-dried again to obtain bilayer cross-linked collagen scaffold. (4) The double-layer cross-linked collagen scaffold is placed in a vacuum oven and subjected to deoxygenated thermal cross-linking for 12-18 hours at 100-115℃ and vacuum degree ≤0.05bar to obtain a collagen scaffold biological patch for wound repair.
7. The method for preparing a collagen scaffold biological patch for wound repair according to claim 6, characterized in that: The MES / ethanol buffer in step (3) is a mixture of MES buffer and anhydrous ethanol, with a volume ratio of MES buffer to anhydrous ethanol of (1-2.5):1, wherein the molar concentration of MES buffer is 0.05-0.1M and the pH is 5.5; the molar ratio of EDC·HCl to collagen carboxyl groups is (3-8):1, and the molar ratio of NHS to EDC is (0.4-0.6):
1.
8. The method for preparing a collagen scaffold bio-patch for wound repair according to claim 6, characterized in that: The mass concentration of the genipin solution in step (3) is 0.2%-0.5%, and a mixture of ethanol and PBS is used as the solvent, wherein the volume ratio of ethanol to PBS is 3:7 and the pH value is 7.2-7.4.
Citation Information
Patent Citations
Collagen-based artificial skin with three-layer composite structure and preparation method of collagen-based artificial skin
CN115518201A
Injectable hydrogel for rapid hemostasis and antibiosis of oral cavity as well as preparation method and application of injectable hydrogel
CN119679995A